Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1103/physrevb.72.014205
|View full text |Cite
|
Sign up to set email alerts
|

Maxwell-Garnett mixing rule in the presence of multiple scattering: Derivation and accuracy

Abstract: We give a rigorous and original derivation of the Maxwell-Garnett mixing rule in the dynamical regime for a composite dielectric random medium with small spherical inclusions. For certain configurations of scatterers, we show that contrarily to the common belief, the Maxwell-Garnett formula can remain very accurate at a high concentration of scatterers and incorporate multiple-scattering effects as well as attenuation of the mean field. We provide a realistic numerical example for which this is the case

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 34 publications
0
108
0
1
Order By: Relevance
“…This was discussed in detail in Ref. 26. There is also a close connection with the low-frequency formula of the EFA 8 for lossless particles ͑␤ s Љ=0͒ which coincides analytically to within the O͑␤ s 2 ͒ term:…”
Section: ͑41͒mentioning
confidence: 92%
“…This was discussed in detail in Ref. 26. There is also a close connection with the low-frequency formula of the EFA 8 for lossless particles ͑␤ s Љ=0͒ which coincides analytically to within the O͑␤ s 2 ͒ term:…”
Section: ͑41͒mentioning
confidence: 92%
“…The Maxwell-Garnett theory is only applicable when encountering low volume fractions of material, typically below the percolation threshold or a volume fraction below 30% (Claro & Rojas, 1991;Datta et al, 1993;Davis & Schwartz, 1985;Gibson & Buhrman, 1983;Grechko et al, 2000;Lamb et al, 1980;Li et al, 2006;Lidorikis et al, 2007;Stroud & Pan, 1978;Wang et al, 2005;Yannopapas, 2006). However, other papers have demonstrated that the Maxwell-Garnett effective medium theory will work for higher volume fractions (Fu et al, 1993;Mallet et al, 2005). The Maxwell-Garnett dielectric function is defined by the expression:…”
Section: Optical Absorption In Metallic Nanoparticle Compositesmentioning
confidence: 99%
“…A less drastic assumption is obtained from the Maxwell-Garnett theory (P. Hillion, 2010;Tsang & Kong, 2001;Mallet, Guerin, & Santenac, 2005) in which, the permittivity  of a composite material is…”
Section: Remarkmentioning
confidence: 99%